Дослідження імовірності виникнення ризику та аналіз зловмисних програм - Пестєрєва, С. Є. (ХНУРЕ, 2020)
The technological advances in computing devices have created great impact for wide range of application. Since computing devices may be coupled with third-party software applications, so, many security and privacy difficultiescan be stimulated by malwares. Object of research - methods to improve safety for computer systems as for home users and business users. The purpose of this work is a research malware and threat analysis. Build classification certain malware.